The Systemic Inflammatory Response Syndrome and Predictors of Infection and Mortality in 1068 Critically Ill Newborn Foals - Pamela A. Wilkins; David Wong; Nathan M. Slovis; Niamh Collins; Bonnie S. Barr; Catriona MacKenzie; Cristobal Navas De Solis; Carolina Castagnetti; Jole Mariella; Teresa Burns; Gillian Perkins; Barbara Delvescovo; et al. (Journal of Veterinary Internal Medicine)
ABSTRACT Background Sepsis has been defined in humans as the concurrent proven or suspected presence of microbial infection and the systemic inflammatory response syndrome (SIRS). Sepsis is the leading cause of morbidity and mortality in neonatal foals. The clinical utility of using SIRS or its individual components to predict infection and mortality in critically ill foals is currently unknown. Objectives Assess the ability of history and signalment, clinical findings, laboratory results, and SIRS‐related indices to predict infection and mortality in critically ill foals. Animals Retrospective, multi‐center, cross‐sectional study using a convenience sample of 1068 critically ill foals < 3 days of age admitted to 16 veterinary referral hospitals in 4 countries. Methods Data were retrieved from medical records. Infection was defined as the presence of bacteremia (positive blood culture) or clinical identification of an infected focus on admission. Univariate non‐parametric and categorical methods, multivariate logistic regression, and classification tree methods were used for statistical analysis. Results Foal age at admission and presence of toxic neutrophils were independent predictors of infection, whereas SIRS‐related indices were not predictive of infection. In‐hospital mortality was 24%. Independent predictors for mortality were hypokinetic pulses, cold extremities, presence of seizures, blood L‐lactate concentration > 6.0 mmol/L, and increased serum potassium and total bilirubin concentrations. Conclusions and Clinical Importance The presence of infection in critically ill newborn foals was not predicted by SIRS indices. Cardiovascular dysfunction was strongly associated with mortality, suggesting that maintaining adequate perfusion and pulse pressure should be important treatment goals.